The Implementation of Accounting Digitalization and Internal Control on the Quality of Financial Reports - Asmira, Neri; Sulkiah, Sulkiah (E-Jurnal Akuntansi; Vol 35 No 6 (2025), 2025)
This study aims to empirically examine the implementation of accounting digitalization and internal control on the quality of financial reporting among MSMEs in East Lombok. The sample consista of 100 MSMEs selected as the sample from a population of 14,132 MSMEs that consistently maintain financial records. This study utilized purposive smpling for data collection and applied the Partial Least Squere (PLS) method for data analysis. The finding reveal that accounting digitalization does not have a statistically significant positive effect on financial reporting quality. In contrast, internal control exhibits a significant and positive influence on the quality of financial reports. While digitalization can support financial procedures, the findings imply that MSMEs have not yet maximized the potential of this technology. On the other hand, the implementation of effective internal control systems contributes to minimizing errors and fraudulent activities, thereby enhancing the accuracy and reliability of MSMEs’ financial reporting. Keyword: Digital Accounting, Internal Control, Financial Reporting Quality, SMEs